Evaluasi Kualitas Air Sungai Kemambang Berdasarkan Aspek Fisika-Kimia dan Makroinvertebrata sebagai Bioindikator: Indonesia - Munfarida, Ida; Navratilova, Frisda Desyana; Oktorina, Sarita (Jurnal Sains & Teknologi Lingkungan, 2025)
Kemambang River is located in Buduran Sub-district, Sidoarjo and plays an important role in the hydrological cycle and the lives of the surrounding community. Buduran sub-district is one of the sub-districts with high population growth. The number of industries, housing, agriculture around Kemambang River can reduce the water quality of Kemambang River. The purpose of this study was to evaluate the water quality of Kemambang River based on chemical physical parameters and macroinvertebrates as bioindicators of water quality. The research used descriptive quantitative method by conducting water sampling in 3 (three) locations, laboratory tests and analyzing physico-chemical parameters (DO, TSS, BOD, and COD) based on PP 22 Year 2021 class II quality standards and biomonitoring analysis using Family Biotic Index (FBI). The results of the physico-chemical parameter analysis showed that the Biochemical Oxygen Demand (BOD) parameter exceeded the quality standard at all research locations with the highest value at point 3 with a value of 7.10 mg/L (BOD quality standard of 3 mg/L). Dissolved Oxygen (DO) did not meet the quality standards at points 2 and 3 with the lowest value at point 3 with a value of 2.68 mg/L (minimum DO quality standard of 4 mg/L). While the Chemical Oxygen Demand (COD) and Total Suspended Solid (TSS) parameters still met the quality standards at all points. Based on the FBI calculation, point 1 produced a value of 7.20 and was included in the "poor" criteria, while points 2 and 3 with values of 5.32 and 5.40 were classified as "fair" criteria. It concluded that there were significant and very significant amounts of organic pollutants in the waters. This study illustrates the need for urgent action to improve water quality in Kemambang River.